Gestão pública de resíduos sólidos industriais: uma avaliação institucional no complexo industrial e portuário do Pecém - Silva, Lucineide Alves da (2017)
Due to large-scale production, the management of solid industrial waste has become a concern and problem to be solved by the public power and society. From this perspective the paper analyzes the public management of solid industrial waste from an industrial and port complex located in Northeast Brazil. The qualitative, descriptive and exploratory research was carried out by the Pecém Industrial and Port Complex (CIPP), located between the municipalities of Caucaia and São Gonçalo do Amarante, in the metropolitan region of Fortaleza, Ceará State. Using as an evaluation tool the Institutional Analysis and Development (IAD) framework, the research discusses the institutional configuration of the public actors and the instruments of public management of industrial solid waste adopted in the Complex. The data collection of this research was carried out through semi-structured interviews with fifteen key actors, with a questionnaire composed of twenty-two questions, which provided information about the structural conditions of the network of public institutions that somehow contribute the development of the CIPP, the attributes of the actors investigated, the rules in use, as well as interactions, evaluation criteria around the problematic experienced by the actors and the results that have been obtained. It was also carried out a survey of information about legislation, programs, projects and actions of public power related to the management of industrial solid waste in the CIPP. The results showed that the public network needed to control and supervise the management of solid industrial waste in the CIPP is disjointed. The biophysical conditions of the CIPP region are fragile and are at environmental risk; the actors present an activity contained in solid industrial waste management and, in general, they act by provoking society around the theme; the norms in solid industrial waste management do not present wide applicability, with low degree of innovation; there are no interactions in public power for GRSI; there are barriers that hamper evaluation criteria on the problem and the interface between government plans is reduced. The public power, because it is little mobilized around the problem, does not know the benefits of working with aspects related to the instruments that motivate the industries to structure Eco Industrial Parks and to adopt the system of Industrial Symbiosis.